Determining Information on Cardiology Disease Risk Factors of Disease in Women. (3rd July 2014) - Yalçınöz Baysal, Hasret; Bilgin, Sonay; Cantekin, Işın; Bilgin, Gökhan
Abstract : In an attempt to decrease the rate of mortality from cardiovascular diseases, first cardiovascular risk factors should be controlled. This study was carried out to reveal the level of knowledge about cardiovascular disease risk factors in women who presented to a primary healthcare center in Erzurum, Turkey, and the prevalence of such risk factors. Our study is a descriptive one and its data were collected between February and April 2013. The study included 168 women who presented to Filiz Dolunay Family Healthcare Center and who met the criteria and agreed to participate in the study. It was found that 22.6% of the women did not exercise at all above normal range, 53.6% of them had weights above normal, 23.8% smoked, and 22% had hypertension, type 2 diabetes, cholesterol, or excess fat around their waist. It was concluded that, although women were knowledgeable, they did not put this into practice in their lives.